The Pasikrata sanctuary at demetrias and the alleged funerary sanctuaries of Thessaly - Stamatopoulou, M (Université de Liège, Département des Sciences de l'Antiquité, 2014)
Archaeological and epigraphical evidence suggests that cult places existed near or within Thessalian cemeteries of the Classical and Hellenistic periods. Some, especially at Pherai and Demetrias, have been characterized by scholars as ‘funerary’ because of their location within a burial ground, and because of the supposed ‘chthonian’ nature’ of the venerated deities. This paper will focus on the so-called Pasikrata sanctuary at Demetrias, situated in the southern cemetery of the city, and investigated by A.S. Arvanitopoulos between 1912–1915 under the auspices of the Archaeological Society of Athens. Alongside the presentation of the evidence, which is based on the study of the archival material and of a large part of the finds, the focus will be on the discussion of the location of the sanctuary, the type/character of the finds, the nature of the venerated deities and the re-interpretation of the suburban sanctuaries of Thessaly.